Impact of Digital Tools to Attend to Educational Diversity - Quichimbo, Danilo Marcelo Diaz; Asqui, Jeferson Dario Crespo; Maliza, Veronica de Lourdes Lligalo; Campos, Miguel Eduardo Vásconez (Journal of Ecohumanism, 2025)
In contemporary society, digital tools are the best allies of teachers, since they contribute to the generation of learning in harmony with the needs of students. This research aims to analyze the impact of digital tools to address educational diversity in students of the Master’s Degree in Education, Major in Pedagogy in Digital Environments at a public university in Ecuador. A methodology was used based on the mixed approach that combined the quantitative with the qualitative; This was supported by a descriptive study that allowed the assessment of the diversity present in the students. As a methodology, action research was used, which allowed the prominence of the educational subjects. The techniques used were the survey, interview, and observation aimed at educational actors. The results showed that collaborative digital tools allow assessment from the diversity of age, gender, religion, in adherence to values ​​and principles. As conclusions, it is highlighted that digital tools must be framed in a sequenced process to achieve learning objectives in response to the diversity presented by teachers.